PENERAPAN PEMBELAJARAN INQUIRY TERBIMBING UNTUK MENINGKATKAN MOTIVASI DAN HASIL BELAJAR TEMATIK SELAMATKAN MAKHLUK HIDUP TERHADAP PESERTA DIDIK KELAS VI - Sitti Bahrah; Nasaruddin Nasaruddin (JPPSD:Jurnal Pendidikan dan Pembelajaran Sekolah Dasar, 2022)
This study aims to (1) increase learning motivation in saving living things thematically through the application of guided inquiry learning to students of class VI UPTD SD Negeri 100 Barru, (2) knowing the improvement of thematic learning outcomes save living things through the application of guided inquiry learning to students. class VI UPTD SD Negeri 100 Barru. This research is a classroom action research conducted in 2 cycles. The research subjects were 21 students of class VI UPTD SD Negeri 100 Barru in Semester One of the Academic Year 2021/2022. Indicators of research success are motivation and learning outcomes increase by meeting the criteria of classical minimum completeness, Actions taken to improve and increase student learning motivation and learning outcomes in each cycle by: (1) applying Guided Inquiry learning, (2) providing motivation to students groups to be more active in participating in each activity in learning, (3) grouping students based on the results of learning outcomes tests and arranging the location of each group in learning, (4) directing each group member to help each other understand the material. The results showed that there was an increase in motivation and thematic learning outcomes to save living things through the application of guided inquiry learning to students of class VI UPTD SD Negeri 100 Barru.